High subsequent and recurrent sexually transmitted infection prevalence among newly diagnosed HIV-positive Thai men who have sex with men and transgender women in the Test and Treat cohort. (February 2019) - Hiransuthikul, Akarin; Pattanachaiwit, Supanit; Teeratakulpisarn, Nipat; Chamnan, Parinya; Pathipvanich, Panita; Thongpaen, Suchart; Pengnonyang, Supabhorn; Trachunthong, Deondara; Nonenoy, Siriporn; Lertpiriyasuwat, Cheewanan; Phanuphak, Praphan; Phanuphak, Nittaya
We determined subsequent and recurrent sexually transmitted infections (STIs) among men who have sex with men (MSM) and transgender women (TGW) in the Test and Treat cohort. Thai MSM and TGW adults with previously unknown HIV status were enrolled and tested for HIV. Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and syphilis were tested at baseline, month 12, and month 24 to identify subsequent STIs (any STIs diagnosed after baseline) and recurrent STIs (any subsequent STIs diagnosed among those with positive baseline STIs). Among 448 participants, 17.8% were HIV-positive, the prevalence of subsequent STIs and recurrent STIs was 42% (HIV-positive versus HIV-negative: 66.3% versus 36.7%, p < 0.001) and 62.3% (81% versus 52.5%, p < 0.001), respectively. Common subsequent STIs by anatomical site were rectal CT infection (21.7%), rectal NG infection (13.8%), pharyngeal NG infection (13.1%), and syphilis (11.9%). HIV-positive status was associated with both subsequent STIs (adjusted hazard ratio [aHR] 2.38; 95%CI 1.64–3.45, p < 0.001) and recurrent STIs (aHR 1.83; 95%CI 1.16–2.87, p = 0.01). The results show that newly diagnosed HIV-positive MSM and TGW were at increased risk of STIs despite being in the healthcare system. STI educational counseling is necessary to improve STI outcomes among MSM and TGW in both HIV prevention and treatment programs.